Heart rate and blood lactate concentration as training indicies for high level men's gymnasts - Jemni, M.; Sands, W. A.; Friemel, F.; Le Chevalier, J.-M. (2003)
The data here elucidate the metabolic requirement through the course of a gymnastics competition and show the differences between events. The anaerobic requirement is very important in four events contrary to what it used to be considered. Blood lactate concentration remained not negligible seeing mean overage above lactate threshold. The lactate concentration differed between apparatuses. Vaulting lactate value, as well as its heart rate, were significantly smaller than those of the other exercises. Floor routines induced the highest lactate production, followed in decreasing order by 1) rings and pommel horse, 2) horizontal bar and 3) parallel bars. Heart rate response was strong during gymnastic exercises. These values should not be used as a direct indication of effort intensity. By knowing such indices, coaches could prescribe individual training programs at each phase of the season such as the competitive one in which gymnasts usually have to repeat their six events two to five times in one session. The effect of one exercise on another and the short recovery duration between events may cause coaches to think also about using active recovery. This has been done in many other sports. Our next study will examine a variety of recovery models during gymnastics` session.